O comportamento informacional de bibliotecários(as) frente às fake news: uma análise de participantes do grupo “bibliotecários do Brasil” no Facebook - Santos, Josué Pereira da Silva (2021)
The survey discusses fake news concepts and uncontextualized information in digital social media. It is evident in the theoretical notes the concepts of communication, information and social networks presented by Castells (2013; 2016), McLuhan (1964), Lamb (2017), Flusser (2007), Santos and Rossini (2014), as well as concepts of behavior and informational skills from authors Wilson (1981; 1999; 2000), Kulhthau (1991), Choo (2003), Dervin (1983), Taylor (1968), Belkin (1978) and Ellis (1989), discusses the differences of post-truth, misinformation and fake news from the authors Corrêa e Custódio (2018), D'Ancona (2018), Wardle and Derakhshan (2017), Paula, Silva and Blanco (2018), relating the behaviors and attitudes demanded of the librarian from the perspective of the challenges faced against the fake news in the group "Bibliotecários do Brasil" on Facebook. The aim of this research is to analyze the informational behavior of the librarians of the group "Bibliotecários do Brasil" on Facebook, in the face of the spread of fake news. It uses the qualitative approach to establish the case study of the informational behavior of librarians with a view to verifying the behavior of these professionals on Facebook. It adopts the methodological characterization of case study proposed by Mascarenhas (2012) to investigate the studied community. It establishes as a data collection tool the questionnaire with members, interview with administrators and observation of posts and interactions in the group "Bibliotecários do Brasil" on Facebook. It seeks to list the informational behavior of these librarians and the criteria adopted in sharing information in digital social media. It justifies the realization of this research in the interest of the researcher, considering the advancement of fake news, highlighting the importance of criteria for the search, evaluation and use of information by librarians against social networks and the media as a way to counteract misinformation in the information age. It lists as a result that librarians recognize the importance of using criteria in the search for credibility information, yet it is found that the behavior of these professionals in checking information does not become routine. Identify and analyze suspicious publications posted between the proposed period for analysis from 15 March 2020 until 30 September 2020, considering the period of pandemic caused by Sars-CoV 2. It is concluded that most librarians identify, establish and understand the importance of checking information before sharing, but still some of these professionals have shared information without establishing criteria for analysis.